Macroencapsulation Devices for Cell Therapy. (June 2022) - Liu, Wei; Wang, Yanfang; Wang, Jinqiang; Lanier, Olivia L.; Wechsler, Marissa E.; Peppas, Nicholas A.; Gu, Zhen
Abstract: Macroencapsulation has been widely used in cell therapy due to its capability to provide immune-privileged sites for implanted allogeneic or xenogeneic cells. Macroencapsulation also serves to provide mechanical and physiochemical support for maintaining cell expansion and promoting therapeutic functions. Macroencapsulation devices such as membrane-controlled release systems, hydrogels, microneedle (MN) array patches, and three-dimensional (3D) stents have shown promising in-lab and preclinical results in the maintenance of long-term cell survival and the strengthening of treatment efficacy. Recent studies focus on expanding the applications of these devices to new cell-based areas such as chimeric antigen receptor (CAR)-T cell delivery, cardiovascular disease therapy, and the exploration of new materials, construction methods, and working principles to augment treatment efficacy and prolong therapy duration. Here, we survey innovative platforms and approaches, as well as translation outcomes, for advancing the performance and applications of macrodevices for cell-based therapies. A discussion and critique regarding future opportunities and challenges is also provided.